SISTEM INFORMASI PROSES AKUNTASI MENGGUNAKAN SAK-ETAP BERBASIS WEB PADA PELAKU USAHA - Puspita Rama Nopiana (LPPM Universitas Abdurrab, 2018)
The number of entrepreneurs in question is SMEs (Small and Holding Enterprises), where its activities only focus on business operations alone tampa pay attention to financial performance for the long term. This causes the difficulty of SMEs to last long in building their business, plus the lack of knowledge in the field of accounting, especially SMEs in the city of Batam. The purpose of the research is to design an accounting process information system in accordance Financial Accounting Standards Entity Without Public Accountability (SAK-ETAP) on the small business actors. The research method used is the experiment to design the process of information system of accounting process of companies engaged in services, trade and manufacturing. The results explain that the accounting process information system in the preparation of financial statements are needed SMEs, which currently presenting financial statements are still presented manually. The information system designed in the form of accounting software is named Financial Statement Information System Standardized Entity Without Public Accountability abbreviated with